2014
DOI: 10.1186/s40478-014-0146-2
|View full text |Cite
|
Sign up to set email alerts
|

Frequent and symmetric deposition of misfolded tau oligomers within presynaptic and postsynaptic terminals in Alzheimer’s disease

Abstract: The accumulation of neurofibrillary tangles in Alzheimer’s disease (AD) propagates with characteristic spatiotemporal patterns which follow brain network connections, implying trans-synaptic transmission of tauopathy. Since misfolded tau has been shown to transmit across synapses in AD animal models, we hypothesized that synapses in AD patients may contain misfolded tau. By immunofluorescence imaging of bipartite synapses from AD subjects, we detected tau protein in 38.4% of presynaptic and 50.9% of postsynapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
78
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 60 publications
(69 reference statements)
8
78
1
Order By: Relevance
“…A high frequency of axon terminals, and of dendritic spines (> 85%) contained pS214-tau, which was present in presynaptic and postsynaptic compartments of the same synaptic complex in over three-quarters of synapses, and across age and treatment groups. These findings are in line with those of another recent study wherein~80% of bipartite neocortical synapses from nondemented elderly control and AD subjects alike were identified as tau-positive (Tai et al, 2014). Like our own observations, modified tau protein (e.g., hyperphosphorylated) was also abundantly distributed on both sides of the synapse.…”
Section: Frequency Of Synapses Containing Ps214-tausupporting
confidence: 93%
“…A high frequency of axon terminals, and of dendritic spines (> 85%) contained pS214-tau, which was present in presynaptic and postsynaptic compartments of the same synaptic complex in over three-quarters of synapses, and across age and treatment groups. These findings are in line with those of another recent study wherein~80% of bipartite neocortical synapses from nondemented elderly control and AD subjects alike were identified as tau-positive (Tai et al, 2014). Like our own observations, modified tau protein (e.g., hyperphosphorylated) was also abundantly distributed on both sides of the synapse.…”
Section: Frequency Of Synapses Containing Ps214-tausupporting
confidence: 93%
“…Furthermore, we demonstrate that synaptogenic mechanisms also promoted Tau pathology dissemination within an artificial neuronal network. The presence of abnormal Tau within the pre-and post-synaptic compartments of AD brains supports the idea that this species can be a substrate for trans-synaptic transmission (Tai et al, 2014). We therefore hypothesize that a form of Tau-seeding species that is present at the synapse can be trans-synaptically transmitted to connected neurons, thereby disseminating Tau pathology by inducing aggregation of soluble Tau (Guo and Lee, 2014;Tai et al, 2014).…”
Section: Discussionmentioning
confidence: 72%
“…Whereas we cannot point toward a single mechanism, it is feasible that cell death is reduced while neuronal population is protected by MGF treatment. In this line, it has been suggested that misfolded tau at synapses may represent early signs of neuronal degeneration and mediate synaptotoxicity (51). At central level, tau hyperphosphorylation is a marker of neuropil dysfunction observed in neurodegenerative diseases, including AD and VaD (10,48).…”
Section: Discussionmentioning
confidence: 99%
“…Early alterations, and not necessarily tangles, may contribute to cognitive malfunction (23). In this line, it has been suggested that misfolded tau at synapses may represent early signs of neuronal degeneration and mediate synaptotoxicity (51). Also, autopsy studies have reported brains with neurofibrillary tangles that are indistinguishable from those of AD, in the absence of amyloid plaques, usually associated with mild cognitive impairment (8).…”
Section: Discussionmentioning
confidence: 99%